SISTEM INFORMASI PERSEDIAAN BAHAN BAKU PADA A LOT OF COFFEE - Dedy Apriadi; Uro Abdulrohim; Samzul Abidol (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2020)
A Lot Of Coffee is a Coffee shop that serves various types of coffee in the archipelago. In carrying out its business processes are growing, not a few obstacles experienced by A Lot Of Coffee. The problems that often occur in A Lot Of Coffee is the difficulty of storing raw material data processing that relies on the archive because of the absence of special storage for raw material data, so that raw material data is often lost or damaged, frequent recording of raw materials are repeated, and existing raw material data is not stored properly. Therefore, this company needs a raw material inventory information system that can help operate all its work activities, so as not to the loss of raw materials data and archives of the company. System development method used is Water Fall method where data collection techniques used include interviews and observations. With the construction of raw material inventory information system is expected to facilitate the company in the process of recording raw materials and raw material data archiving so as to minimize the possibility of error in input data and minimize the loss of data archive company. Keywords: Information System, Supply of raw materials, material, product